2015
DOI: 10.1097/cad.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the wild-type and mutant K-ras increases the resistance to 5-flurouracil in HCT-116 as a colorectal cancer cell line

Abstract: Colon cancer is the second to third common cancer worldwide. Several efforts have been made to reveal the pathways responsible for drug resistance in this type of cancer. We aimed to investigate the effect of silencing both mutant and wild-type Kristen Rous sarcoma (k-ras) on the response of human colorectal tumor 116 (HCT-116) as a colon cancer cell line to the cytotoxic effect of 5-flurouracil (5-FU). One oligonucelotide against mutant k-ras (12th codon, namely 207) and two against wild-type k-ras (namely 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Since the K-ras gene was reported to be inhibited by let-7 family in various cancers (Büssing et al, 2008;Johnson et al, 2005), it could be used as a potential target gene in tumor therapy (Teimoori-Toolabi et al, 2015) to slow proliferation and tumor growth of lung cancer cells (Esquela-Kerscher et al, 2008;Kumar et al, 2008;Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since the K-ras gene was reported to be inhibited by let-7 family in various cancers (Büssing et al, 2008;Johnson et al, 2005), it could be used as a potential target gene in tumor therapy (Teimoori-Toolabi et al, 2015) to slow proliferation and tumor growth of lung cancer cells (Esquela-Kerscher et al, 2008;Kumar et al, 2008;Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, mutations in APC contribute to 5-FU resistance in colon cancer cells [25]. Furthermore, silencing wild-type and mutant KRAS enhances the resistance to 5-FU in colon cancer cell lines [26]. Therefore, the further validation of the effect of eupatilin in colon cancer cells with genetic mutation will lead to conclusive evidence suggesting that eupatilin can exert a therapeutic effect in combination treatment with conventional chemotherapy in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiences showed that siRNAs closer to the start codon are more efficient than farther ones. 22 Based on the algorithm by Reynolds et al, the sequence preferences of the sense strand are influential on the siRNA efficiency. Reynolds studies on the sense strand showed that the presence of A at the third position and U at the tenth position, A at the nineteenth position, besides the absence of G or C at the nineteenth and G at the thirteenth nucleotide potentiate the silencing effect of siRNA.…”
Section: Discussionmentioning
confidence: 99%